Lipid profile and socioeconomic status in healthy middle aged women in Sweden. Issue 4 (August 1997) - Wamala, S P; Wolk, A; Schenck-Gustafsson, K; Orth-Gomér, K
Abstract : STUDY OBJECTIVE: To examine the relationship between socioeconomic status (SES) and full lipid profile in middle aged healthy women. PARTICIPANTS: These comprised 300 healthy Swedish women between 30 and 65 years who constitute the control group of the Stockholm female coronary risk study, a population based, case-control study of women with coronary heart disease (CHD). The age matched control group, drawn from the census register of greater Stockholm, was representative of healthy Swedish women aged 30-65 years. Five measures of SES were used; educational level, occupation, decision latitude at work, annual income, and size of house or apartment. MAIN RESULTS: Swedish women with low decision latitude at work, low income, low educational level, blue collar jobs, and who were living in small houses or apartments had an unhealthy lipid profile, suggesting an increased risk of CHD. Part of this social gradient in lipids was explained by an unhealthy lifestyle, but the lipid gradients associated with decision latitude at work and annual income were independent of these factors. Decision latitude, educational level, and annual income had the strongest associations with lipid profile. These associations were independent of age, menopausal status, smoking, sedentary lifestyle, alcohol consumption, obesity, excess abdominal fat, and unhealthy dietary habits. Of the lipid variables, low high density lipoprotein cholesterol (HDL) levels were most consistently associated with low SES. CONCLUSIONS: Decision latitude at work was the strongest SES predictor of HDL levels in healthy middle aged Swedish women, after simultaneous adjustment for other SES measures, age, and all lifestyle factors in the multivariable regression model.